Validation and characterization of murine gammaherpesvirus 68 antisense transcripts by northern blot analysis and quantitative reverse transcription-PCR - Kara, Mehmet (Archives of Biological Sciences, 2023)
Paper description: Large DNA viruses such as herpesviruses have compact and gene-dense genomes. They generate many different transcript isoforms including non-coding RNAs. Studies on viral non-coding RNAs based on quantitative PCR analysis that measures gene expression quantitatively are inadequate to understand the transcriptional complexity of these viruses. Murine gammaherpesvirus 68 was utilized to present several antisense transcript isoforms generated from a complex region in the genome, including very large read-through transcripts. Northern blotting provided results that could be used to design functional analysis experiments for generating mutants and creating antisense oligos for the target of interest. Abstract: The transcription of mammalian genomes exhibits an intriguing complexity and numerous novel RNA molecules have been identified. Viruses with large DNA genomes, especially herpesviruses, generate many different RNA species, including long non-coding RNAs (lncRNAs). Dense viral genomes can generate multigenic transcripts in addition to commonly observed antisense transcripts. It is essential to study the biological roles of these transcripts aside from the protein-coding counterparts. Multiple antisense transcripts from the open reading frame (ORF) 63-64 locus in murine gammaherpesvirus 68 (MHV68) were detected by northern blotting. Expression analysis by quantitative reverse transcription PCR (qRT-PCR) did not detect different isoforms. Several alternative splicing isoforms exist during lytic replication; however, they are not detected during latency. To identify the roles of these new transcripts, qRT-PCR may not be enough and should be supported by an alternative method such as northern blotting. A more detailed transcriptional map of the locus of interest is useful to design experimental strategies and perform functional studies, especially when working with gene-dense viral genomes.